Post-COVID-19 severe cholangiopathy: report of 6 cases - Santisteban Arenas, Marco Tulio (2022)
Coronavirus disease 2019 (COVID-19) is a predominantly respiratory tract infection with the capacity to affect other organs. Liver chemistry abnormalities are a frequent manifestation of COVID-19 but are usually transient. We describe the clinical course and most relevant findings of 6 patients who developed a cholangiopathy after severe COVID-19. The mean age of the patients, 4 men and 2 women, was 56 years and the mean time from COVID-19 diagnosis to diagnosis of cholangiopathy was 138 days. The features most important were the increase of alkaline phosphatase and destructuring and beading of the intrahepatic bile duct in magnetic resonance imaging. Cholangiopathy after severe COVID-19 constitutes a novel entity with unique features and po ondary biliary cirrhosis. Further studies are required to understand this disease.